2017
DOI: 10.1038/labinvest.2016.135
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblastic foci, covered with alveolar epithelia exhibiting epithelial–mesenchymal transition, destroy alveolar septa by disrupting blood flow in idiopathic pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive interstitial lung disease of unknown cause. IPF has a distinct histopathological pattern of usual interstitial pneumonia in which fibroblastic foci (FF) represent the leading edge of fibrotic destruction of the lung. Currently there are three major hypotheses for how FF are generated: (1) from resident fibroblasts, (2) from bone marrow-derived progenitors of fibroblasts, and (3) from alveolar epithelial cells that have undergone epithelial-mesenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 31 publications
1
59
0
Order By: Relevance
“…However, we have uncovered that FF are localized between them, and push the preexisting capillaries and elastic fibers down approximately 100 µm below the epithelia (Fig. ) reveals that although FF are covered with alveolar epithelia that are uniformly and mostly positive for CK7 and TTF‐1, respectively, some alveolar epithelia over FF are flat rather than round, express vimentin, and lose TTF‐1 expression .…”
Section: The Origin Of Ff Observed In Ipfmentioning
confidence: 89%
See 3 more Smart Citations
“…However, we have uncovered that FF are localized between them, and push the preexisting capillaries and elastic fibers down approximately 100 µm below the epithelia (Fig. ) reveals that although FF are covered with alveolar epithelia that are uniformly and mostly positive for CK7 and TTF‐1, respectively, some alveolar epithelia over FF are flat rather than round, express vimentin, and lose TTF‐1 expression .…”
Section: The Origin Of Ff Observed In Ipfmentioning
confidence: 89%
“…) reveals that although FF are covered with alveolar epithelia that are uniformly and mostly positive for CK7 and TTF‐1, respectively, some alveolar epithelia over FF are flat rather than round, express vimentin, and lose TTF‐1 expression . This suggests that some alveolar epithelia covering FF appear to have acquired a partial EMT phenotype.…”
Section: The Origin Of Ff Observed In Ipfmentioning
confidence: 97%
See 2 more Smart Citations
“…Peptidyl‐prolyl cis / trans isomerase (Pin1) was shown to induce HuR to bind and stabilize TGF‐β mRNA resulting in enhanced collagen expression and peribronchiolar fibrosis in mice . Studies have indicated that EMT occurring within the alveolar epithelium plays a key role in fibrotic lung remodeling in this disease . Surfactant protein C (SFTPC) is a key component of lung surfactant, which maintains alveolar epithelial function and integrity .…”
Section: Rna‐binding Proteins: Mrna Decay and Translation Initiationmentioning
confidence: 99%